Disability in the Christian Tradition: Overview and Historiographic Reflection - Yong, Amos (Journal of religion, disability & health, 2013)
This article summarizes and overviews Brian Brock and John Swinton's Disability in the Christian Tradition: A Reader (2012), and reflects on its contribution from a historiographic perspective. In particular, this discussion explores how the lens of disability invites new approaches to the history of the Christian tradition that opens up fresh perspectives on narrating Christian history, recounting the history of Christian thought, and reconsidering the theological legacies of major thinkers.